2011
DOI: 10.1007/s11162-011-9222-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Destinies: Improving Opportunity for Low-Income Students in American Higher Education

Abstract: Recognizing the current administration's focus on improving postsecondary access, this study examines resource allocation patterns and the predictive power of these resources in increasing the likelihood of 2-and 4-year college enrollment among lowincome students. Using data from the Educational Longitudinal Study, college choice decision-making is conceptualized in relation to an individual's habitus and capital deficiency theory. The results reveal significant differences in the availability and predictive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
1
44
0
2
Order By: Relevance
“…Even when examining a group of students who successfully matriculated to a four-year, non-profit college immediately upon graduation, there are significant differences among lowand high-SES students in relation to institutional selectivity, particularly among the most academically prepared students. While access remains a critical social justice issue and postsecondary education is far from universal (Engberg & Allen, 2011), this study demonstrates that stratification patterns in postsecondary enrollment remain even when comparing students with equivalent academic qualifications. Bastedo and Jacquette (2011) have also shown that despite overall increases in the academic preparation of low-SES students over time, they have been outpaced by even more substantial gains in academic preparation among high-SES students.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Even when examining a group of students who successfully matriculated to a four-year, non-profit college immediately upon graduation, there are significant differences among lowand high-SES students in relation to institutional selectivity, particularly among the most academically prepared students. While access remains a critical social justice issue and postsecondary education is far from universal (Engberg & Allen, 2011), this study demonstrates that stratification patterns in postsecondary enrollment remain even when comparing students with equivalent academic qualifications. Bastedo and Jacquette (2011) have also shown that despite overall increases in the academic preparation of low-SES students over time, they have been outpaced by even more substantial gains in academic preparation among high-SES students.…”
Section: Discussionmentioning
confidence: 81%
“…More effort is needed in recruiting students from lower socioeconomic backgrounds, particularly those who are admitted to a highly selective school. Research has shown that low-income students who meet with a college representative (Engberg & Allen, 2011) or receive financial information (Cabrera & La Nasa, 2001) are significantly more likely to attend college (Engberg & Allen, 2011), yet admission counselors are more likely to establish relationships with high schools in high-income neighborhoods (Wolniak & Engberg, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations